2021
DOI: 10.1002/app.50520
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured rigid polyurethane foams with improved specific thermo‐mechanical properties using bacterial nanocellulose as a hard segment

Abstract: Rigid polyurethane foams (RPUFs) were synthesized with bacterial nanocellulose (BNC) at concentrations of up to 0.5 wt% using two insertion routes based on its reaction with the isocyanate precursor (ISO route) and the formation of a colloidal dispersion in the polyol precursor (POL route). The results indicated that, for BNC concentrations of only 0.1 wt%, drastic improvements of the specific elastic compressive modulus (+244.2%) and strength (+77.5%) were measured for foams with apparent density of 46.4+/− 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 55 publications
5
5
0
Order By: Relevance
“…In fact, for the case of immersion at 25°C, we can observe that increasing contents of BNC caused a monotonous increase of cell size in the L direction, which was the exactly opposite case in the T direction. These results reinforce the hypothesis that BNC was increasing the anisotropic behavior of the foams, 14 causing more heterogeneity in the variation of cell size.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…In fact, for the case of immersion at 25°C, we can observe that increasing contents of BNC caused a monotonous increase of cell size in the L direction, which was the exactly opposite case in the T direction. These results reinforce the hypothesis that BNC was increasing the anisotropic behavior of the foams, 14 causing more heterogeneity in the variation of cell size.…”
Section: Resultssupporting
confidence: 88%
“…It is important to highlight that, in all cases, water immersion produced and increased amount of open cells, but, the observation of the micrographs of the pristine foams clearly indicated that BNC acted as a cell opener. Such result were completely logical and it has already been observed by our group as well as other researchers 14,35,55,56 . Nowadays, it is known that BNC has a substantial role in the formation and rupture of cell windows during foaming and this aspect is clearly affected by the insertion route 14,39 .…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations